The impact of climate change on small-scale fishermen in Malaysia - Muhammad, Mahazan; Idris, Khairuddin; Ariffin, Effi Helmy; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Suandi, Turiman (Medwell Journals, 2016)
This study aims to conceptually discuss the impacts of climate change on small-scale fishermen in Malaysia. Based on the document analyses made, it was concluded that Malaysia is also experiencing the impacts of climate change similar to other countries in the world. This impact of climate change has brought negative implications towards several community groups and the small-scale fishermen are one of them. Climate change is found to have increased several risks associated with fishing activities, affect their productivity, health and damage to the public facilities. A number of adaptation strategies were recommended and it is hope to assist the related parties in constructing the best adaptation strategies to overcome the rising climate change in Malaysia.